Internet: media manipulation and new myths in postmodern Western society - Brenes-Sánchez, Jeff (2021)
This article explores the role the media plays in the transformation of myths and the construction of alternate realities in the context of postmodern Western society. Theoretical tools of critical analysis are implemented in order to explain the purpose of myths today and how, from these mythical discourses, reality gets manipulated. It begins with a postmodern myth that is still current as a mean to show that myths have never disappeared. That is, the idea that science and reason are the only valid ways to explain reality; but this discourse hides the fact that technological means of communication have become modern spaces for the creation of new heroes and distorted social realities. In the end, it is concluded that postmodern Western society supplants old myths with other paradigmatic models that arise from the creation of these manipulated realities and how social subjects (individual or collective) assume an active place in the emergence of these new paradigms whose value, unlike the ones from ancient eras, is not in the conduct they represent but in the profits they can generate.